One-Roof School Management of Remote, Underdeveloped and Isolated Schools A Case Study of One-Roof Elementary School-Junior High School of Prampelan - , Samsudin, Prof. Dr. Harsono, SU (2011)
The objectives of research are to describe (1) the characteristics of leadership of the principal of One-Roof State Elementary School-Junior High School of Prampelan, Kaliangkrik District, Magelang Regency, (2) the characteristics of facilities and infrastructures of One-Roof State Elementary School-Junior High School of Prampelan, Kaliangkrik District, Magelang Regency, (3) the characteristics of the financial policy of One-Roof State Elementary School-Junior High School of Prampelan, Kaliangkrik District, Magelang Regency. It is descriptive qualitative research and ethnographic design. The research was conducted in One-Roof State Elementary School-Junior High School l of Prampelan, Kaliangkrik District, Magelang Regency. The main subject of the research is the principal, teachers, and employees of One-Roof State Elementary School-Junior High School of Prampelan, Kaliangkrik District, Magelang Regency. The data collection methods uses depth interviews, participatory, observation, and documentation. Analysis of data using data analysis model are arranged in a site to be described. Test the validity of data using credibility, transferability, conformabilities' and dependability. The research results show that (1) the leadership of the principal still follow the old pattern or traditional, teacher's job description at the beginning of the school year, the leadership of the principal must follow the instruction and guidelines from the government, the leadership of the principal walk like water flow, low resistance honorarium and future GTT staffing, the number of elementary and secondary school heads meeting, leadership consists of one principal, one vice-principal, assisted by the Head of Curriculum, Head of Student Affairs, Head of Facilities and Infrastructures, Head of Public Relations and Administration, to finance carried out by treasurer. (2) facilities and infrastructures of the building and equipment, land used for the three educational institutions of kindergarten, elementary and junior high school is a village government grants, school buildings were apprehensive about, facilities and infrastructures are used by two institutions, teacher's lack of mastery of the barrier material and the material, not good inventory lack of storage space, there is no fence around, is reduced because the number of students exceeding the standard. (3) finance policy uses the traditional way of free education funded by the BOS, the financial manager dealt with the treasurer, the guidelines and instructions, the use of finance have been on their own, there are no reports of internal constraints and not reporting to their respective parents or guardians, schools and school committee still need funds.